PENGARUH KECERDASAN EMOSIONAL DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA GURU SMA DAN SMK NEGERI DI KOTA BANDUNG - Ayu Nike Retnowati; Rifna Alfiyah Hasanah (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
The educational process would never be separated from the role of teachers as educatior . For students, a teacher will be a helpful part of teaching and learning. Teachers are also one of the professionals who contribute to improving a country's human resource quality. Assessment of performance is one of the controls for maintaining the quality of instruction. The purpose of this study is to identify the description of Emotional Intelligence and Interpersonal Communication on Teacher Performance, as well as the amount of their influence on the performance of SMA and SMK Negeri teachers in Bandung. The descriptive verification with a quantitative approach was employed as the research method in this study. SMA and SMK Negeri in the city of Bandung, has a total of 43 schools and 2,829 instructors. In this study, 141 instructors from ten different schools made up the sample. Probability sampling with Cluster Random Sample methodology was utilized as the sampling method. Emotional Intelligence, Interpersonal Communication, and Teacher Performance were all determined to be in the good group, according to the study's findings. Results Emotional Intelligence had a 48.1% effect on teacher performance, Interpersonal Communication had a 33.1% effect on teacher performance, and Emotional Intelligence plus Interpersonal Communication had a 52.8% effect on teacher performance, according to the determination test.